2005
DOI: 10.1007/s00268-005-7849-2
|View full text |Cite
|
Sign up to set email alerts
|

Technetium‐99m‐MIBI SPECT/CT in Primary Hyperparathyroidism

Abstract: The novel trend toward focused parathyroidectomy requires precise preoperative localization of the parathyroid adenoma in patients with primary hyperparathyroidism (PHPT). The present study evaluated the impact of hybrid single photon emission computed tomography/computed tomography (SPECT/CT), using 99mTc-sestamibi (MIBI), on the surgical management of these patients. In a retrospective study of 36 patients with PHPT, SPECT/CT was undertaken when planar 99mTc-MIBI scintigraphy was negative or when an ill-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
1
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 32 publications
3
92
1
8
Order By: Relevance
“…Also, Gayed et al reported that SPECT/CT was only of limited value (8% of patients) (48). On the contrary, a retrospective study indicated a change in therapeutic management for 39% of patients (14/36) because of the localization of ectopic parathyroid adenomas or accurate localization in patients with distorted neck anatomy (49). Because of some inconsistent reports, a definite role of SPECT/CT in the imaging of parathyroid adenomas has not yet been indicated, and evaluations with larger patient cohorts are needed.…”
Section: Spect/ct In Parathyroid Tumorsmentioning
confidence: 99%
“…Also, Gayed et al reported that SPECT/CT was only of limited value (8% of patients) (48). On the contrary, a retrospective study indicated a change in therapeutic management for 39% of patients (14/36) because of the localization of ectopic parathyroid adenomas or accurate localization in patients with distorted neck anatomy (49). Because of some inconsistent reports, a definite role of SPECT/CT in the imaging of parathyroid adenomas has not yet been indicated, and evaluations with larger patient cohorts are needed.…”
Section: Spect/ct In Parathyroid Tumorsmentioning
confidence: 99%
“…The task presents an additional obstacle due to the close vicinity of the thyroid gland which affects the precision of the examination (pinpointing voxel position) [24]. In these circumstances proposing a relatively simple, repeatable method of focal lesion metabolic activity assessment, as is the case with TBR, allows a much more precise differentiation of these foci.…”
Section: Discussionmentioning
confidence: 99%
“…Deux études récentes ont montré que la P-TEMP/TDM s'avère surtout utile pour préciser la localisation des LP ectopiques ou des LP orthotopiques après remaniements post chirurgicaux de la région cervicale ou en l'absence de thyroïde [41][42]. L'information morphologique de la TDM …”
Section: Discussionunclassified